FINANCIAL LITERACY AND SUSTAINABLE CAPITAL MARKET FOR INCLUSIVE ECONOMIC EMPOWERMENT - Debbi Chyntia Ovami; Toni Hidayat; Lisa Septia Dewi Br. Ginting; Noor Marini Haji-Abdullah; Siti Aminah; Muhamad Bagas Reziqo (RADJA PUBLIKA, 2026)
This service focuses on improving financial literacy and understanding of sustainable capital markets for inclusive economic empowerment. In the context of Indonesia and Malaysia, low financial literacy and lack of understanding of sustainable capital markets limit public participation in the formal economy. Therefore, this service aims to provide knowledge about personal financial management, sustainable investment, and access to capital markets that can drive inclusive economic growth. This service aims to improve financial literacy and understanding of sustainable capital markets to empower an inclusive economy in Indonesia and Malaysia, with a focus on MSMEs and the general public. Through the stages of planning, implementation of socialization, and training, participants are given knowledge about basic financial management, business management, and sustainable investment. The service method involves a classical and individual approach as well as the active participation of partners in each stage. The targeted outputs include increasing public knowledge about financial literacy and sustainable capital markets, as well as empowering MSMEs in accessing sustainable funding, scientific articles, videos and media news. Outcomes include increased financial literacy, better financial management, and MSMEs' access to sustainable capital markets, which contribute to inclusive economic growth and the achievement of the SDGs.